Pelatihan Manajemen Keuangan Digital Bagi Pelaku UMKM Dalam Menghadapi Persaingan Bisnis Online - Rizky Mery Octavianna Lubis; Yusuf Pathuansyah; Ade Maya Mei Shanty; Nurdelila (Yayasan Perguruan Kampus, 2025)
This study aims to examine the implementation and impact of digital financial management training for Micro, Small, and Medium Enterprises (MSMEs) in facing the increasing competition of online business. The training was designed to improve digital financial literacy and enhance the capacity of MSME actors in using financial applications to manage their business finances more systematically and efficiently. Using a qualitative descriptive approach with participatory action methods, this program involved 30 MSME participants from various sectors and was conducted through stages of needs assessment, core training, and post-training mentoring. The results indicate significant improvement in participants’ understanding of basic financial concepts, their ability to use digital financial applications (such as BukuKas and Excel), and their confidence in making business decisions based on financial data. Moreover, the training succeeded in shifting participants’ mindset regarding the importance of financial management and opened opportunities for financial inclusion through formal access to capital. Despite challenges in consistency and digital infrastructure, this training has proven to be an effective strategy to strengthen the competitiveness and sustainability of MSMEs in the digital economy era.